Contribution of Inhibition to Stimulus Selectivity in Primary Auditory Cortex of Awake Primates - Sadagopan, Srivatsun (Society for Neuroscience, 2010)
Recent studies have demonstrated the high selectivity of neurons in primary auditory cortex (A1) and a highly sparse representation of sounds by the population of A1 neurons in awake animals. However, the underlying receptive field structures that confer high selectivity on A1 neurons are poorly understood. The sharp tuning of A1 neurons' excitatory receptive fields (RFs) provides a partial explanation of the above properties. However, it remains unclear how inhibitory components of RFs contribute to the selectivity of A1 neurons observed in awake animals. To examine the role of the inhibition in sharpening stimulus selectivity, we have quantitatively analyzed stimulus-induced suppressive effects over populations of single neurons in frequency, amplitude, and time in A1 of awake marmosets. In addition to the well documented short-latency side-band suppression elicited by masking tones around the best frequency (BF) of a neuron, we uncovered long-latency suppressions caused by single-tone stimulation. Such long-latency suppressions also included monotonically increasing suppression with sound level both on-BF and off-BF, and persistent suppression lasting up to 100 ms after stimulus offset in a substantial proportion of A1 neurons. The extent of the suppression depended on the shape of a neuron's frequency-response area (“O” or “V” shaped). These findings suggest that the excitatory RF of A1 neurons is cocooned by wide-ranging inhibition that contributes to the high selectivity in A1 neurons' responses to complex stimuli. Population sparseness of the tone-responsive A1 neuron population may also be a consequence of this pervasive inhibition.